No man's nightingale : an Inspector Wexford novel - Rendell, Ruth, 1930-2015. (Hutchinson, 2013)
"A female Vicar named Sarah Hussein is discovered strangled in her Kingsmarkham Vicarage. The gossipy cleaning woman who discovers her body, Maxine, happens to also be in the employ of retired Chief Inspector Wexford and his wife. When detective inspector Mike Burden calls him, Wexford, intrigued by the unusual circumstances of the murder, leaps at the chance to tag along with the investigators. A single-mother to a teenage girl, Hussein was a woman working in a male-dominated profession. Moreover, she was of mixed race and working to modernize the church. Could racism or sexism played a factor in her murder? As he searches the Vicar's house with Buren, Wexford sees a book on her bedside table. Inside the book is a letter serving as a bookmark. Without thinking much, Wexford puts it into his pocket, Wexford soon realizes he has made a grave error - the former policeman has taken away a piece of valuable evidence without telling anybody. What he finds inside begins to illuminate the murky past of Hussein. Is there more to her than meets the eye? No Man's Nightingale is the captivating twenty-fourth installment in Rendell's masterful Wexford series, which has been delighting readers for almost half a century"--